2019
DOI: 10.3390/molecules24091706
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Metabolites and Antiradical Activity of Liquid Fermentation of Morchella sp. Isolated from Southwest China

Abstract: Morels famous for their taste and nutrition are in short supply all over the world although they were considered as one of the most highly prized edible and medicinal mushrooms. Because of the limitation of resource and cultivation technology, fermentation of edible mushroom was gradually applied to nutrient, bioactivity and breeder seed preparation. At present, there are more reports on sugar and amino acid but less on other components. Morchella sp. YDJ-ZY-1 was isolated from the wild fruiting body by the sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 14 publications
2
6
0
Order By: Relevance
“…Structures of adenosine and herierin III were elucidated via the obtained NMR spectral data, including 1D ( 1 H and 13 C NMR) and 2D NMR [correlation spectroscopy (COSY), heteronuclear single quantum correlation (HSQC), heteronuclear multiple bond coherence (HMBC)]. Spectral data are in agreement with those reported in the literature for structural elucidation of adenosine [ 30 ] and herierin III [ 31 ]. The complete NMR data assignments of both compounds were summarised in Additional file 1 .…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…Structures of adenosine and herierin III were elucidated via the obtained NMR spectral data, including 1D ( 1 H and 13 C NMR) and 2D NMR [correlation spectroscopy (COSY), heteronuclear single quantum correlation (HSQC), heteronuclear multiple bond coherence (HMBC)]. Spectral data are in agreement with those reported in the literature for structural elucidation of adenosine [ 30 ] and herierin III [ 31 ]. The complete NMR data assignments of both compounds were summarised in Additional file 1 .…”
Section: Resultssupporting
confidence: 75%
“…ex Pers. [ 31 ], Hericium americanum Ginns , Hericium abietis (Weir ex Hubert) K.A. Harrison and Hericium alpestre Pers.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, AMRL 52 and AMRL 63 mycelia achieved the highest TP content of 18.4% and 15.4% of dried biomass in PP and WG–PP, respectively. Previous studies have identified the bioactive compounds [60] deriving from Morchella mushrooms, showing that their functional properties are related to beneficial effects on human health [20,21,61]. The present results demonstrate the perspective for the production of bioactive compounds, such as glucosamine and polysaccharides, from Morchella sp.…”
Section: Resultssupporting
confidence: 70%
“…The most recent studies have demonstrated that polysaccharides from Morchella sp. present antioxidant [20,21] and antitumor [22] properties. Additionally, sclerotia from mushrooms are considered as an exceptional source of bioactive components characterized for their functional and medicinal properties, such as antitumor and anti-inflammatory activities.…”
Section: Introductionmentioning
confidence: 99%
“…Edible fungi consumed fresh or processed are becoming more and more vital in the human diet due to their unique dietary and medical properties. High carbohydrate, protein, low-fat content and the composition of dietary fiber along with the taste and aroma make edible mushrooms an ideal source of nutrition, rich in minerals and vitamins [1][2][3][4][5]. Furthermore, edible mushrooms are characterized by antitumor, cardiovascular, anti-inflammatory and anti-allergenic properties due to their variety of secondary metabolites in their fruiting bodies including polysaccharides, phenolic compounds and antioxidants [6,7].…”
Section: Introductionmentioning
confidence: 99%